Estudos de nanotubos de carbono e de titanatos e suas aplicações em reações de oxidação - Eudes Lorencon (2012)
The aim of this work was the development of new catalysts and adsorbents based on carbon nanotubes decorated with gold and titanate nanotubes toward their applications in the removal of sulfur compounds from fuels. This work is divided into six chapters, where the first chapter describes the general objectives, motivation and organization of work. The following chapters having everyone its own introduction, procedures, results and conclusions. In the chapter 2, carbon nanotubes and titanate nanotubes were synthesized and characterized. Single-walled carbon nanotubes (SWNTs) were prepared by arc discharge method. Multi-walled carbon nanotubes (MWNTs) were produced in a CVD system, using ferrocene as precursor. The purification of these materials occurred through thermal oxidation followed by hydrochloric acid treatment. The inorganic titanate nanotubes, both in the sodium titanate(Na2Ti3O7) and hydrogen titanate (H2Ti3O7) forms were prepared by simple alkaline hydrothermal treatment of TiO2 anatase. In the chapter 3 several synthetic approaches for production of the hybrids between carbon nanotubes and metal nanoparticles were studied. The resultsindicated that in all routes studied there was formation of gold nanoparticles on carbonaceous surface. Nevertheless, the method developed in this work, based on the metal nanoparticles formation through reduced carbon nanotubes showed better results in terms of particle size and distribution. In the chapter 4 the thermal behavior of the decorated and purified carbon nanotubes was investigated by thermogravimetric analysis and differential thermal analysis. The results indicated that Au and Pd nanoparticles on the carbon nanotubes surface can catalyze carbon oxidation. This catalytic effect is strongly related with the average of metal particles size. In the chapter 5, the catalytic activity of titanate nanotubes and carbon nanotubes decorated with gold was evaluated in the oxidation of probe molecule methylene blue (MB) in the hydrogen peroxide presence. These results revealed that the titanate nanotubes and carbon nanotubes decorated with low Au particle size (ca. 5.9 nm), are efficient catalysts for the AM oxidation in the hydrogen peroxide presence. The interaction of these materials with hydrogen peroxide was investigated in detail by various techniques, includingelectron paramagnetic resonance (EPR). In both cases were proposedmechanisms for the oxidation processes. In chapter 6 the carbon nanotubes decorated with gold and titanate nanotubes were applied in the removal of sulfur compounds (dibenzotiofeno) form simulated matrix of oil (cyclohexane). Two different approaches for sulfur removal were tested, the adsorption and oxidative desulfurization. The adsorption studies revealed that only the CNT/Au with low particle size, produced by polyelectrolyte salt method, showed a significant increase in thesulfur adsorption capacity due to specific interactions between Au anddibenzotiofeno. In oxidative desulfurization can be demonstrated that thehydrogen titanate nanotubes showed excellent catalytic performance under mild conditions, with high turnover number and elevated recuperation rate. Through kinetic studies, the reaction mechanisms have been proposed.